Teacher Strategies in Instilling Students Social Attitudes Through Learning Natural and Social Sciences in Class IV Elementary School - Erik Aditia Ismaya; Imaniar Purbasari; Frindy Putri Rahmawati (STKIP Taman Siswa Bima, 2024)
This research aims to determine how teachers carry out science learning in Class IV Elementary School in instilling social attitudes in students. Social attitudes are a person's tendency to interact with the people around him and the way they perceive him. Children's social attitudes are greatly influenced by their environment, and the school environment is one of them. The research was conducted at SD Negeri Bancak 01 in February 2024, and the subjects were class IV students and class teachers. Data collection was carried out through interviews, observation and documentation. The data analysis used is reduction, presentation and drawing conclusions. Data validity techniques use source triangulation, technique triangulation and time triangulation. The research results found that teachers have instilled social attitudes through science learning. The social attitudes found were honesty, discipline, responsibility, tolerance, mutual cooperation, politeness and self-confidence. During science learning, teachers try to instill social attitudes in students by getting students to practice social attitudes, relate them to the material, and provide direction.